Puerto Real island beach resort complex - Peñamante, Annaliza A. (Manila : National University, 2001)
There are no other species in this world that are wiser and more createful than we human are. As we approach the next century worldwide thrust for economic reforms and technological progress seems to be the utmost consideration even for small third world countries. Commerce and international trade supported by political stability is the key to success in the rush to be ahead in the new century? In the Philippines evidences that can be gleamed all over the country where the number of local and international trade business establishment have multiplied are apparent. The number of domestic and international visitors is increasing so thus the pressures on some of the countries unique natural resources. It seem self evident that it is the tourism industry interest to insure that such resources are manage in a manner which protect intrinsic values.
Title page -- Letter of endorsement -- Jury's Approval sheet -- Acknowledgement -- Dedication -- Chapter I. Introduction -- Chapter II. Methodology -- Chapter III. Review of Related literature -- Chapter IV. Design framework -- Chapter V. Analysis -- Chapter VI. Summary, conclusions and recommendations.
Includes bibliographical references.
Keywords: RESORT -- COMPLEX